Pengaruh Pendekatan Scientific Terhadap Kemampuan Penalaran Matematis Siswa Kelas X IPA Di SMA Negeri 11 Medan - Nurul Izza; Wingston Leonard Sihombing (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to determine whether there is an effect of the scientific approach on the mathematical reasoning abilities of class X IPA students at SMA Negeri 11 Medan. The population in this study were all students in class X SMA Negeri 11 Medan which consisted of 10 classes, namely 360 students. Of the 10 classes randomly selected, class X IPA 6 was an experimental class that was taught using a scientific approach, and class X IPA 7 was selected as a control class that was taught using conventional learning. This type of research is quantitative research. The data collection instrument was in the form of a posttest in the form of a description, which consisted of 5 validated questions. Data analysis in this study used the SPSS 20 application. Before testing the hypothesis, the normality test was first tested using the Kolmogorov-Smirnov test and the homogeneity test using the homogeneity of variance test and the data linearity test. From the tests carried out, it was found that the data in the study of the two samples came from populations with normal, homogeneous, and linear distribution, thus the authors could provide treatment to both samples. The results of the study after being treated for two meetings, namely in the experimental class taught using the scientific approach obtained an average value of 90.17 and the control class taught using conventional learning obtained an average value of 74.17. To test the hypothesis, a simple linear regression test was used from the results of the calculations, then obtained an F count of 73.579 a significance level of 0.000